Hubungan Antara Body Mass Index (BMI) dan Pengalaman Karies pada Anak Pra-Sekolah di Puskesmas Rawang - Dini Chairani Prima; Murniwati Murniwati (Andalas Dental Journal, 2016)
influence dental caries due to altered saliva composition and impaired secretion. Intake of foods rich in carbohydrates can be risk factor for overweight, obesity and tooth decay. BMI is considered a simple method to analyse a nutritional status. Purpose: The aim of this study is to determine the relationship between BMI and caries status of preschool children in Puskesmas, Rawang District of Padang City. Method: This study used the cross sectional design, with the total sample were 72 students from 6 from Early Childhood Development Place (PAUD) which located in Puskesmas Rawang, and selected through proportionate stratified random sampling method. The analysis of the relationship between BMI (underweight, normal weight, and obese) and caries status is conducted with Kruskal Wallis’ Test and followed by Mann-Whitney’s Test. Result: Ultimately, this study shows that there are significant differences (p <0.05) between BMI (underweight, normalweight, and obesity) and caries status, which for the category of underweight-obesity showed significant difference (p<0.05), whereas in the category of underweight-normalweight and normalweight-obesity showed there is no significant differentiation (p <0.05). The results of this study indicated that the highest score of caries is in the categories of underweight children.Conclusion: As the conclusion of this study revealed that there is a relation between Body Mass Index (BMI) and Caries Status. Keywords: Body Mass Index (BMI), Caries